Angiogenesis, fibrinogenesis and presence of synechiae after exeresis of a swine vocal fold mucosal microflap and use of topical mitomycin-C - Fonseca,Vinicius Ribas de Carvalho Duarte (2010)
PURPOSE: To evaluate swine vocal fold healing in a period of 30 days after topical mitomycin-C application. METHODS: Twelve swine underwent exeresis of mucosal flaps from the free edge of the anterior third of both vocal folds with a cold instrument (laryngeal scissors). The animals were divided into two groups: EG (Experimental Group), consisting of 6 animals undergoing topical MMC application (4 mg/dL) on the operated area for 4 minutes; CG (Control Group), 6 animals undergoing topical saline solution application on the operated area for 4 minutes. After 30 days, the animals were sacrificed and the larynges were collected and examined for the presence of synechiae as well as a histological immunohistochemical assessment of immature and mature collagen deposition, number of blood vessels and myofibroblasts. RESULTS: Mature collagen deposition in the EG was 452.12 μm² and 1332.31μm² in the CG; immature collagen deposition was 1511.73μm² in the EG and 1020.61μm² in the CG. The number of myofibroblasts was 1.556 in the EG and 3.583 in the CG. The number of blood vessels was 2.565 in EG and 6.917 in the CG. There were no synechiae in the two studied groups. CONCLUSIONS: There was an increase in immature collagen deposition in the experimental group when compared with the control group. There was a decrease in mature collagen deposition in the experimental group when compared with the control group. There was a decrease in the number of myofibroblasts in the experimental group when compared with the control group. A decrease in blood vessels was observed in the experimental group when compared with the control group. There was no synechia formation in either studied group.